Gender-specific differences in mental health literacy and influencing factors among residents in Foshan City, China: a cross-sectional study - Chu, Zhaosong; Xie, Jianling; Liu, Rui; Ou, Liqin; Lan, Zheng; Xie, Guojun (Frontiers in Public Health, 2025)
BackgroundMental health literacy (MHL) is essential for enhancing mental well-being and addressing mental health challenges. In China, MHL levels remain low, and studies on gender differences in MHL are limited. This study aims to explore gender-specific differences in MHL and their influencing factors among residents of Foshan City, China, to provide a theoretical basis for targeted mental health interventions.MethodsData for this study were obtained from the 2022 Foshan City Residents’ Mental Health Survey. A comprehensive sample of 9,044 participants over 18 years old was included, collecting information on sociodemographic characteristics, lifestyle habits, health-related factors, and MHL assessments. Chi-square (χ2) tests and independent samples t-tests were used to analyze gender differences in MHL. Additionally, multi-factor logistic regression analysis was conducted to identify factors influencing MHL across genders.ResultsThe overall MHL attainment rate was 8.46%. Male residents demonstrated a significantly lower attainment rate of 6.65%, compared to 10.14% among female residents. Across specific dimensions, including mental health knowledge, attitudes, and psychological skills, males consistently exhibited lower levels of MHL than females. Multi-factor logistic regression analysis identified protective factors for male MHL, including higher educational attainment, professional technical occupations, and retirement, while depression emerged as a significant risk factor. For females, protective factors included higher education, higher monthly household income, and engaging in exercise 3 to 5 times per week. Risk factors for females included being middle-aged or older and experiencing depression.ConclusionThe MHL levels among residents of Foshan City are relatively low, with notable gender differences, particularly with males exhibiting significantly lower levels compared to females. These findings highlight the ongoing necessity to enhance the dissemination and accessibility of mental health knowledge. When developing relevant policies as well as measures, it is imperative to take into account gender differences and implement tailored programs aimed at enhancing MHL among both male and female residents.